PENERAPAN MODEL PEMBELAJARAN INKUIRI DALAM MENINGKATKAN KEMAMPUAN MENGANALISIS TEKS EKSPOSISI PADA SISWA KELAS X.1 SMA PGRI 4 DENPASAR - Ida Ayu Agung Ekasriadi; Putu Dessy Fridayanthi; Gusti Ayu Made Puspawati (LP3M Universitas PGRI Mahadewa Indonesia, 2024)
Expository text has the aim of providing an explanation or description of an idea, main idea, opinion, information or knowledge to the reader without the intention of influencing it. However, there are still students who are not able to analyze expository text correctly. The aim of this research is to find out whether the application of the inquiry learning model in analyzing expository texts can improve students' abilities and students' responses to the application of the inquiry learning model in improving the ability to analyze expository texts in class X students. This type of research is classroom action research. The subjects of this research were students in class This research uses two cycles and each cycle consists of planning, action, observation, evaluation and reflection. Data collection techniques use test and observation methods. Data collection in cycle I and cycle II was carried out using the technique of assessing student test results as numerical data, while data collection used observation techniques for qualitative data. The research results show that the application of the inquiry learning model can improve students' ability to analyze exposition texts and the application of the inquiry learning model can increase the responses of class X.1 students at SMA PGRI 4 Denpasar in the 2023/2024 academic year in analyzing exposition texts